Detection of seepage paths in small earth dams using the self-potential method (SP) - Netto, Leonides Guireli; Filho, Walter Malagutti [UNESP]; Gandolfo, Otávio Coaracy Brasil (FapUNIFESP (SciELO), 2020)
The application of geoelectric methods, such as induced polarization (IP), the electrical resistivity and the self-potential (SP), presents an important indirect study methodology in several areas of geology, such as mining, geotechnics and environmental geology. The present study deals with the results of the application of the self-potential method (SP) in small earth dams in the cities of Cordeirópolis and Ipeúna, both in the state of São Paulo. Studies of the Engineering of Dams intensified at the end of century XX, due to alarming number of dam disruptions. In Brazil, small dams are still the majority, around 90% of the total. This article presents results of surveys of the self-potential in two small dams, analyzing the flow of fluids, heat or ions inside the dams, as well as possible areas of percolation or water saturation. Three lines of 78 meters each were made with a spacing of 2 meters between the electrodes in the Cordeirópolis dam, and three lines of 122 meters each, spaced 2 meters between the electrodes in the Ipeúna dam. In both collections, the potential technique (or fixed base) was used. The collected data was worked on 2D maps of self-potential, which allowed to identify the zones with greater and smaller values of potential difference, preferential flow of the subsurface fluids in the areas, and possible problems in the structure of the dam (seepage paths), which could affect the physical integrity of the structure.
Keywords: Dam inspection; Geophysics in dams; Self-potential; Subsurface flow